Evacuation of aircraft on land - Jevtić, Radoje B. (Vojnotehnički glasnik / Military Technical Courier, 2022)
Introduction/Purpose: Aircraft present one of the safest and most frequently used means of transport. However, despite taking many security measures, accidents happen. No matter a damage level, if the aircraft somehow manages to land, the most important is to evacuate passengers from the aircraft, fast and safely. Evacuation of aircraft is very complex and depends on many different factors such as a damage degree, presence of fire, speed of passengers, presence of panic and fear, etc. So, it is important to, somehow, as much as possible, predict potential ways of evacuation and potential evacuation strategies and routes. Landed aircraft can be in different conditions so fast and safe evacuation of passengers is very important. The only way to predict safe evacuation routes, to determine proper evacuation strategies and to calculate potential evacuation times needed to leave the aircraft is to use some adequate simulation software.Methods: In this paper, for calculating needed evacuation times and potential evacuation routes, the simulation method was used. Simulations of evacuation scenarios and calculations of evacuation times were realized in Pathfinder software. The simulation model created in Pathfinder was a model of the A 321 aircraft related to its real dimensions. Results: The results of this paper, obtained on an appropriate simulation model of the aircraft with stairs and emergency slides, have shown the evacuation times for two different evacuation scenarios with different speeds of passengers/occupants.  Conclusion: A proper evacuation strategy and the fastest evacuation of occupants are crucial for saving lives. Simulation software use in evacuation problems presents a very effective way in terms of safety, cost-effectiveness and prediction. This kind of software presents an obligatory engineering tool for more effective and more precise dealing with evacuation and similar problems. This paper was written to show how simulation software can be used for calculating evacuation times from an airplane on land.
Keywords: evacuation; aircraft; simulation; passenger